Pengaruh Konseling Humanistik Terhadap Motivasi Belajar Siswa Kelas X di SMAN 1 Lingsar - Gunawan, I Made (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2016)
The objectives of this research are: to know how big influence on motivation to learn humanistic counseling on subjects Biology class X grade students of SMAN 1 Lingsar, West Lombok in the academic year 2016/2017. This type of research, experimental method with quantitative approach. The data collection technique is a method of inquiry as the principal methods and methods of documentation, observation and interviewing methods/ interview as a complementary method. The statistical analysis used in this research is using t-test formula. Based on the discussion can be concluded that: there is the influence of humanistic counseling on motivation to learn in the subjects of biology class X grade students of SMAN 1 Lingsar, West Lombok in the academic year 2016/2017. It can be seen from the results of the study are: t value of 4,131dan t table value at significance level of 5% with N = 7, is greater than the value t table (4.131> 2.365) so that there is a relationship that is "significant" between counseling humanistic motivation to learn in the subjects of biology class X grade students of SMAN 1 Lingsar, West Lombok in the academic year 2016/2017.